THE EFFECT OF CLASSROOM MANAGEMENT ON STUDENTS’ LEARNING ACTIVENESS AT SD NEGERI LAMPEUNEURUT ACEH BESAR - Rahima Ahsana; Lailatussaadah Lailatussaadah; Nurmayuli Nurmayuli; Sri Mutia (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
This study aims to examine the effect of classroom management on students’ learning activeness at SD Negeri Lampeuneurut, Aceh Besar. The study employed a quantitative approach using a simple linear regression design. The population consisted of all fifth-grade students totaling 98 students, with a sample of 80 students selected using the Krejcie and Morgan table. Data were collected through a questionnaire measured using a Likert scale and analyzed using regression analysis with SPSS 25. The results showed that classroom management was in the high category with a mean score of 3.85, and students’ learning activeness was also in the high category with a mean score of 3.80. Regression analysis indicated a significant effect of classroom management on students’ learning activeness, as evidenced by a significance value of 0.001 < 0.05, a correlation coefficient of 0.478, and a coefficient of determination of 22.8%. The regression equation Y = 21.963 + 0.690X indicates that every one-unit increase in classroom management increases students’ learning activeness by 0.690 units. Thus, it can be concluded that effective classroom management has a significant positive effect on improving students’ learning activeness at SD Negeri Lampeuneurut, Aceh Besar